Interaction mechanisms between C15 Laves phase clusters and 〈1 1 1〉 dislocation loops in BCC-Fe: An atomistic perspective - Amin Esfandiarpour (Results in Physics)
Small C15 Laves phase clusters are extended interstitial defects that form during collision cascades in body-centered cubic (BCC) iron. Although their stability has been confirmed by ab initio calculations up to a certain size, their interactions with other irradiation-induced defects, such as dislocation loops, remain poorly understood. In this study, we use molecular dynamics (MD) and molecular statics (MS) simulations to investigate the interaction mechanisms between C15 clusters and /2〈1 1 1〉 prismatic dislocation loops in BCC-Fe at elevated temperatures (600–1000 K). By systematically varying the relative size and positioning of these defects, we identify three distinct interaction modes: absorption, repulsion, and confinement. Absorption events lead to a range of outcomes depending on the interaction geometry, including complete merging into 1/2〈1 1 1〉 or 〈1 0 0〉 dislocation loops, or the formation of mixed clusters. Stress field analysis reveals that the nature of these interactions is governed by the overlap of elastic fields, with repulsive or attractive behavior arising from the alignment of tensile and compressive regions. These findings provide new atomistic insights into the role of C15 clusters in microstructural evolution under irradiation and offer valuable input parameters for higher-scale modeling techniques such as object kinetic Monte Carlo (OKMC).